2000
DOI: 10.1088/0954-3899/26/5/330
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive production of high-ptphotons at HERA

Abstract: Abstract. We study the diffractive production of high p t photons at HERA. We have implemented the process as a new hard sub-process in the HERWIG event generator in order to prepare the ground for a future measurement.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Recently, the meron concept has been generalized to fermions [9]. Meron-cluster algorithms have led to a complete solution of the fermion sign problem in a variety of models including non-relativistic spinless fermions [9,10], relativistic staggered fermions [11,12,13] and some models in the Hubbard model family [8,14]. 1 Recently, a meron-cluster algorithm has been used to solve the sign problem that arises for quantum antiferromagnets in an external magnetic field [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the meron concept has been generalized to fermions [9]. Meron-cluster algorithms have led to a complete solution of the fermion sign problem in a variety of models including non-relativistic spinless fermions [9,10], relativistic staggered fermions [11,12,13] and some models in the Hubbard model family [8,14]. 1 Recently, a meron-cluster algorithm has been used to solve the sign problem that arises for quantum antiferromagnets in an external magnetic field [15].…”
Section: Introductionmentioning
confidence: 99%
“…The phase diagram of GNM 3 with various global symmetries at non-zero temperature and density has been studied extensively in [3−10]. More specifically [5,6], it was shown that the thermally induced phase transition of the Z 2 -symmetric model belongs to the twodimensional Ising universality class in accordance with the dimensional reduction scenario [11] which predicts that the long-range behaviour at the chiral phase transition is that of the (d − 1) spin model with the same symmetry, because the IR region of the system is dominated by the zero Matsubara mode of the bosonic field. Outside the non-trivial region the critical properties of the system are described by mean field theory according to the large-N f prediction.…”
Section: Introductionmentioning
confidence: 99%
“…+0.03 −0.08 (syst.). The cross sections were compared to the LLA BFKL predictions [22,23,24], using the HERWIG Monte Carlo with no |t| reweighting, as shown in Fig. 4.…”
Section: Pos(eps-hep 2009)333mentioning
confidence: 99%